TOKOH TOKOH PENDIDIKAN ISLAM - Thaharah, Siti Siris Sikti; Sanjaya, Arita (Proceeding International Seminar of Islamic Studies, 2024)
The title of this article is an Islamic education figure. Who are the figures in Islamic education? This article aims to enable everyone to know who the figures of Islamic education are, because the role of Islamic education is very important for the nation's next generation, and helps implement learning. The basis used in describing Islamic education figures is the reference source used in internet sources. This data was uploaded using library research. This type of research shows that the concept of figures in Islamic education is to develop an education system.